Training of Resident Ophthalmologists in Cataract Surgery: A Comparative Study of Two Approaches - Argyrios Tzamalis; Lampros Lamprogiannis; Nikolaos Chalvatzis; Chrysanthos Symeonidis; Stavros Dimitrakos; Ioannis Tsinopoulos (Journal of Ophthalmology)
Purpose. To evaluate and compare the efficacy of two different training methods in resident-performed phacoemulsification surgery. Methods. 502 eyes of 467 patients who underwent resident-performed phacoemulsification were included in the study by reviewing their medical records. Residents were allocated into two groups according to the method applied during their training in cataract surgery; Group A included residents that were trained with the “step-by-step” method and Group B those trained with the “one-step” method. Primary outcome was the incidence of main complications, defined as posterior capsular ruptures and/or zonular dehiscence with vitreous loss. Results. Each resident performed a median of 63 phacoemulsification surgeries. A statistically significant difference (p=0.0032) was noted in the main complications rate between the two groups, yielding a mean of 17.3% in Group A and 7.25% in Group B. Other intraoperative complications were not shown to differ statistically significantly between study groups (p>0.05). Among the first 40 surgeries of each resident, main complications rate differed also statistically significantly (p=0.0048) between Group A (21.67%) and Group B (8.5%), while a better surgical performance-yielding statistical significance in Group A (p=0.017) was indicated in both groups between the 20th and the 30th procedure. Conclusions. Training in cataract surgery using the “one-step” method may lead to an improvement in surgical competency, when measured by complications rates and, therefore, to significantly better quality of training for resident ophthalmologists.